Thermoswitchable catalysis controlled by reversible dispersion/aggregation change of nanoreactors in the presence of α-CD polymers. (29th March 2018) - Li, Yinfeng; Hu, Jie; Niu, Chengrong; Leng, Jinghang; Li, Songjun
Abstract: The present work was aimed at preparing a thermosensitive nanoreactor system which could adjust its dispersion/aggregation status according to external temperature change to achieve the switchable catalysis. The mesoporous silica nanoparticle (MSNP) was selected as the framework material of the nanoreactor, and Ag nanoparticles were encapsulated in the mesoporous silica by an in situ reaction. Dodecyl groups were introduced onto MSNP surface, which could transform reversibly between complexation and disassociation with α -cyclodextrin (CD) cavity upon temperature change. It was found that the nanoreactors aggregated and the catalysis was effectively switched 'off' in the presence of CD polymers at low temperature (20 °C). However, when the temperature increased to 50 °C, the nanoreactors redispersed and catalysis successfully switched 'on'.